Systolic shear wave propagation speed as a novel non-invasive marker of myocardial contractility. (4th February 2022) - Bezy, S; Caenen, A; Duchenne, J; Orlowska, M; D"hooge, J; Voigt, JU
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research Foundation Flanders - FWO Background: Shear wave elastography is a novel echocardiographic method that tracks shear wave propagation in the cardiac wall using high frame rate ultrasound. Shear waves can be induced by e.g. aortic valve closure (AVC). The propagation speed of these waves is related to the stiffness of the myocardium. Previous work has suggested that systolic shear wave speed is related to myocardial contractility. The current gold standard reference method for the evaluation of left ventricular (LV) contractility is pressure-volume loop analysis. However, the invasive nature of this method limits its clinical applicability. Purpose: To compare non-invasively assessed shear wave propagation speed after AVC to invasive pressure-volume loop-derived measurements of contractility. Methods: In 12 pigs (31.9 ± 4.3 kg), dobutamine was administered intravenously. Conventional and high frame rate echocardiographic images were acquired simultaneously with invasively measured pressure-volume loops before and after the administration of dobutamine. High frame rate echocardiographic datasets were acquired with an experimental ultrasound scanner at an average frame rate of 1304 ± 115 frames per second. Shear waves after AVC were visualized on M-mode displays along the interventricular septum which were colour coded for tissue acceleration (Figure 1A). The propagation speed was calculated by semi-automatically measuring the spatiotemporal slope of the shear wave. A set of pressure-volume loops were acquired during preload reduction by balloon occlusion of the vena cava inferior. The end-systolic elastance (Ees) of the ESPVR and preload recruitable stroke work (PRSW) were used as measures of contractility. Results: Heart rate (72 ± 20 bpm vs. 105 ± 25 bpm; p < 0.05) and LV ejection fraction (61 ± 4% vs. 74 ± 7%; p < 0.001) significantly increased after the administration of dobutamine, while the LV end-systolic pressure remained similar (92 ± 21 mmHg vs. 106 ± 23 mmHg; p = 0.08). Pressure-volume loop-derived measures of contractility increased during dobutamine infusion (Ees: 1.3 ± 0.5 mmHg/ml vs. 2.1 ±  1.0 mmHg/ml; p < 0.01 and PRSW: 41 ± 25 mmHg vs. 86 ± 23 mmHg; p < 0.01). Likewise, shear wave propagation speed after AVC increased after dobutamine administration compared to baseline (3.1 ± 0.6 m/s vs. 5.3 ± 1.1 m/s; p < 0.001). Shear wave speed after AVC had a strong positive correlation with Ees (r = 0.68; p < 0.001) (Figure 1B) and PRSW (r = 0.65; p = 0.001) (Figure 1C). Conclusions: Systolic shear wave propagation speed is related to invasively determined measurements of LV contractility. The results of this study indicate the potential of shear wave speed after AVC as a novel non-invasive parameter for the assessment of LV contractile function.